Acquired Tracheoesophageal Fistula After Esophageal Atresia Repair - Boybeyi Türer, Özlem (Balkan Med J, 2020)
BACKGROUND: Recurrence of tracheoesophageal fistula is a frequent complication after esophageal atresia repair. Acquired tracheoesophageal fistulas are long new fistulas that are localized at sites that are not typical of the congenital tracheoesophageal fistula. We present four cases to discuss the diagnostic and management challenges concerning various acquired tracheoesophageal fistula localizations. CASE REPORT: We retrospectively evaluated the medical records of patients admitted with acquired tracheoesophageal fistula in the last 5 years. Among the 16 postoperative tracheoesophageal fistulas, 4 were classified as acquired tracheoesophageal fistula. Patients’ admission age ranged from 1 to 8 years. The female to male ratio was 2:2. The presented cases were admitted with recurrent respiratory tract infections, choking, and coughing. The acquired tracheoesophageal fistulas were observed between the esophagus and cervical trachea, between the esophagus and the right bronchus passing through intrathoracic abscess cavity, in the right bronchus, and between the colon conduit and trachea. One of the acquired tracheoesophageal fistulas healed spontaneously, whereas others required surgical ligation. CONCLUSION: Acquired tracheoesophageal fistula most often occurs secondary to local or diffuse mediastinitis. Acquired tracheoesophageal fistula may appear at unusual sites not typical of congenital tracheoesophageal fistula, such as esophagus-to-right bronchus and conduit to trachea. Therefore, the unusual locations of acquired tracheoesophageal fistula should be borne in mind, and patients evaluated and managed more comprehensively.